INNOVATION IN AGRICULTURE: HOW STARTUPS ARE TRANSFORMING THE INDUSTRY - Shygaeva T. K. (Vestnik Issyk-Kulʹskogo universiteta)
The article provides an overview of modern innovations in agriculture, covering issues such as precision farming, vertical farming, smart farms, biotechnology and market digitalization. The key technologies, advantages and challenges of introducing innovations in agriculture are examined. Start-ups in agriculture are important drivers of innovation, providing innovative solutions and technologies that help agricultural businesses increase productivity, reduce costs, improve product quality and reduce negative environmental impacts. The prospects for the development of agricultural technologies are analyzed in the context of increasing productivity, sustainability and efficiency of the industry. Also discussed are several key areas of innovation in agriculture, their impact on the development of the industry and prospects for the use of these technologies in the future, what opportunities innovation brings to agricultural businesses and how these changes contribute to a more sustainable and prosperous agricultural sector.